Moment arm function dictates patella sagittal height anatomy: Rabbit epiphysiodesis model alters limb length ratios and subsequent patellofemoral anatomical development. Issue 3 (22nd May 2020) - Dan, Michael J.; Parr, William C. H.; Crowley, James D.; Oliver, Rema A.; Kai Lun, Kimberley; Lovric, Vedran; Cross, Mervyn; Broe, David; Walsh, William R.
Abstract: Patellofemoral anatomical dysplasia is associated with patellofemoral instability and pain. The closure of the knee physis occurs at the same age as the peak incidence of patellofemoral dislocation. This study determined the effect on the patellofemoral anatomical development in a rabbit epiphysiodesis model. Twenty‐four skeletally immature New Zealand White rabbits were divided into three groups (a) distal femur epiphysiodesis (FE) (b) proximal tibia epiphysiodesis (TE) (c) control; no epiphysiodesis (C) performed at 6 weeks of age. The primary endpoint was shape analysis using three‐dimensional reconstructions of micro‐computed tomographys (CTs) performed at 30 weeks of age. The limb length ratios (femur:tibia) were significantly different for both FE (mean 0.72, SD 0.0381, P < .001) and TE (mean 0.91, SD 0.0383, P < .001) treatment groups compared to control (mean 0.81, SD 0.0073). Patella height, as measured from the most distal point of the patella to the tibial joint surface (modified Caton‐Deschamps measurement), was lower (baja) in the FE and higher (alta) for the TE, compared with the control group. Our findings suggest femoral and tibial shortening can influence the development of the patellofemoral joint, which may be dictated by moment arm function and is potentially responsible for the etiology of patella alta. Future studies are warranted to explore this association further with the view for the development of treatment options for patella alta in human patients.